From research to practice in the design of cooperative systems: results and open challenges : Proceedings of the 10th International Conference on the Design of Cooperative Systems, May 30 - 1 June, 2012 - Masclet, Cedric; Grasso, Maria Antonietta; Boujut, Jean-François; Hassanaly, Parina; Dugdale, Julie (Springer London, 2012)
COOP 2012 is the tenth COOP conference, marking twenty years from the first conference in 1992. In this special anniversary edition we asked researchers and practitioners to reflect on what have been the successes and the failures in designing cooperative systems, and what challenges still need to be addressed. We have come a long way in understanding the intricacies of cooperation and in designing systems that support work practices and collective activities. These advances would not have been possible without the concerted effort of contributions from a plethora of domains including CSCW, HCI, Information Systems, Knowledge Engineering, Multi-agent systems, organizational and management sciences, sociology, psychology, anthropology, ergonomics, linguistics, etc. The COOP community is going from strength to strength in developing new technologies, advancing and proposing new methodological approaches, and forging theories. From Research to Practice in the Design of Cooperative Systems: Results and Open Challenges presents theoretical contributions, empirical studies, systems development and evaluation, and innovative concepts on the following topics: Conceptual frameworks for understanding cooperative work or collective practices Guidelines for designing cooperative systems The influence of technologies (intelligent devices, mobile computing, ubiquitous computing, etc.) on cooperation Expertise, knowledge sharing and learning in cooperative work Communities and new forms of organization Innovative technological solutions and user interfaces for cooperation Methods for participatory design of cooperative systems Applications for, and studies of, social networking (including experiences in industrial contexts) Analysis of collective practices or collaborative work Reports of usage experiences and case studies